Tratamento endovascular da persistência do canal arterial em adulto - Gaia, Diego Felipe [UNIFESP] (2008)
The patent ductus arteriosus (PDA) is a common type of congenital heart defect and its correction is simple when performed early in life. Surgery is performed using stitches or clips. In adults, the anomaly can lead to pulmonary hypertension and ventricular dysfunction. Surgery in adults is controversial and high-risk. This report describes an alternative endovascular approach in an adult patient.